PERAN PENDIDIKAN KARAKTER DALAM MENGHADAPI KRISIS MORAL GENERASI MUDA - Nursalim; Nadilanasir, Filza; Amelia, Lisa; Alya, An Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of the globalization era has had a significant impact on various aspects of life, including the morality of the younger generation. The phenomenon of a moral crisis, marked by increasing deviant behavior such as misuse of technology, promiscuity, and declining respect for social norms and cultural values, is a serious issue that must be addressed immediately. Amid the rise of deviant behavior and the moral crisis affecting young people, instilling positive character traits such as honesty, responsibility, empathy, and discipline has become increasingly relevant. This study aims to provide information about the importance of character education in preventing a moral crisis among the younger generation. Character education is one of the strategic solutions to shape the personality of young people so that they possess strong moral values. The results of the study show that character education is one of the main keys to preventing a moral crisis and forming a generation with integrity.